2013
DOI: 10.1108/14608791311310465
|View full text |Cite
|
Sign up to set email alerts
|

Supportive housing best practices in a mid‐sized US urban community

Abstract: Purpose -Housing First has been upheld as an evidence-based best practice for transitioning homeless individuals into permanent housing in a maximally cost-effective and humane manner. However, there is much variance in the implementation and structure of Housing First programming in the USA. This paper aims to focus on a collaborative, interdisciplinary Housing First effort to house and provide case management and ancillary services to chronically homeless individuals in The City of San Mateo, California.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…Several research teams found savings across the justice system with fewer prison days and police contacts (Basu et al 2012;Chalmers McLaughlin 2011;Goering et al 2014;Greenberg et al 2013;Larimer et al 2009;West et al 2014). Greenberg et al (2013) found that prior to housing, monthly health costs averaged $US195.93 per person per month, and one year after moving into permanent housing, these costs had dropped 85 percent to $US28.98 per month. There were reductions in mental health costs (Chalmers McLaughlin 2011;Goering et al 2014).…”
Section: Theme 4: Cost-effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research teams found savings across the justice system with fewer prison days and police contacts (Basu et al 2012;Chalmers McLaughlin 2011;Goering et al 2014;Greenberg et al 2013;Larimer et al 2009;West et al 2014). Greenberg et al (2013) found that prior to housing, monthly health costs averaged $US195.93 per person per month, and one year after moving into permanent housing, these costs had dropped 85 percent to $US28.98 per month. There were reductions in mental health costs (Chalmers McLaughlin 2011;Goering et al 2014).…”
Section: Theme 4: Cost-effectivenessmentioning
confidence: 99%
“…Reduced criminal reconvictions following stable housing Somers et al (2013) Association between recent incarceration and insecure housing Geller and Curtis (2011) Fewer jail bookings Clifasefi, Malone, and Collins (2013) Less criminal activity/reduced offending DeSilva, Manworren, and Targonski (2011); Srebnik, Connor, and Sylla (2013) Fewer prison days/reduced incarceration Basu et al (2012); Bean, Shafer, and Glennon (2013); Hanratty (2011); Kerman et al (2018); Larimer et al (2009); Srebnik, Connor, and Sylla (2013); Tsai, Mares, and Rosenheck (2010) Reduced police contact/arrests Goering et al (2014); Greenberg et al (2013) violence. Other notable research gaps were older people more generally, refugees, recent migrants, veterans, Indigenous people, and those with a disability.…”
Section: Criminal Justice Prisonmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3, two studies of flexible, individualized, and strengths-based interventions described a positive relationship with participants' relational outcomes, and these referred to HF interventions (Bean et al, 2013;Greenberg et al, 2013). One described project H3, and after 12 months, HF participants had significantly greater social quality of life compared to baseline (Bean et al, 2013).…”
Section: Relational Antecedentsmentioning
confidence: 99%
“…One described project H3, and after 12 months, HF participants had significantly greater social quality of life compared to baseline (Bean et al, 2013). Greenberg et al (2013) examined HF participants' outcomes over time and reported that after 12 months, 87.5% of HF services users strengthened their connections with family and friends, compared to 12.5% at baseline. However, in both studies the sample sizes were small (< 40), and the absence of detail about participants' characteristics made it difficult to rule out attrition bias or other confounding influences.…”
Section: Relational Antecedentsmentioning
confidence: 99%